The effect of an 8-week low- or high-volume protocol of the adductor strengthening programme on hip adduction strength in female football players-A randomized trial - Thorarinsdottir, S.; Isaksen Johansen, S.; Ruud Askim Elvestad, T.; Amundsen, R.; Bache-Mathiesen, L. K.; Bahr, R.; Møller, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The aim of this study was to investigate if an 8-week high-volume protocol of the Adductor Strengthening Programme was more effective than a low-volume protocol in increasing and maintaining isometric hip adduction strength in female football players. We randomized 52 players from the Norwegian women's 1st and 2nd division to a low-volume (220 reps/side) or high-volume (394 reps/side) group. Both groups performed an 8-week protocol of the Adductor Strengthening Programme and a 10-week maintenance protocol with 1 session/week (16 reps/side/session). We measured isometric hip adductor torque (Nm/kg) in a long-lever squeeze test (at 0° and 15° hip abduction) using the ForceFrame at baseline, weeks 4, 6, 8, and 18. Both groups increased their isometric hip adduction strength over the 8-week period (low-volume 0°: 0.13 [95% CI: 0.07-0.20] Nm/kg, 15°: 0.22 [95% CI: 0.07-0.36] Nm/kg; high-volume 0°: 0.13 [95% CI: 0.04-0.22] Nm/kg, 15°: 0.31 [95% CI: 0.18-0.45] Nm/kg), with no between-group difference in either test position (0°: -0.01 [95% CI: -0.11-0.01] Nm/kg; 15°: 0.10 [95% CI: -0.09-0.29] Nm/kg). Also, both groups maintained their strength throughout the 10-week maintenance period, with no between-groups difference in either test position (0°: 0.12 [95% CI: -0.01-0.24] Nm/kg; 15°: 0.06 [95% CI: -0.11-0.23] Nm/kg). Our results indicate that an 8-week high-volume protocol of the Adductor Strengthening Programme was not more effective in increasing isometric adductor strength in female football players than a low-volume protocol. Both groups increased their strength over the 8-week training period and maintained their strength during the 10-week maintenance period.